Academic Stress and Study Habits in Peruvian University Students - Duche-Pérez, Aleixandre; CASALI-TURPO, Janet Rita; PARI-FLORES, Rómulo Elías (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
The current research aims to analyze the relationship between academic stress and study habits in Peruvian university students. A quantitative method was employed, with a non-experimental design, basic research type, and relational level. The study was conducted with a population of 133 students from various specialties at the Faculty of Education of the Catholic University of Santa María in Arequipa, selecting a sample of 99 students for the study. For data collection, two instruments were applied: the Likert scale questionnaire called SISCO Inventory, consisting of 29 questions to assess the level of stress, and another Likert scale questionnaire, called Study Habits Inventory, comprising 53 questions to evaluate the knowledge about study habits. After conducting the correlation between the variables under study, it was determined that there is a very strong inverse correlation between academic stress and study habits, approaching a perfect correlation. The correlation coefficient obtained was r^2 = (-0.840)^2 = 0.706. This indicates that 70.6% of academic stress affects the study habits of students at the School of Education of the aforementioned university. The significance level of this correlation is very strong, implying that the higher the level of academic stress, the worse the study habits of the students, and vice versa.